Impact of Protein-Energy Wasting and Dietary Management on Complications in Chronic Kidney Disease Patients Undergoing Hemodialysis: A Study from Tripoli, Libya - Abuagela, Manal; Essarbout, Nadia (AlQalam Journal of Medical and Applied Sciences, 2025)
Chronic Kidney Disease [CKD] is a severe, widely spread disease that leads to advanced kidney dysfunction, mainly at the advanced stage, necessitating interventions like dialysis or kidney transplantation. Lately, the results clarified that dietary modifications are mandatory to counteract the adverse effects of this disease, particularly for patients experiencing Maintenance Hemodialysis [MHD]. This study aimed to assess CKD patients' awareness and nutritional status under hemodialysis, focusing on the relationship between dietary intake and disease complications and the effects of phosphorus and sodium intake on CKD patients' morbidity and mortality rate. The study conducted Interviews with 111 hemodialysis patients at two Kidney dialysis centers in Tripoli, Libya. The study utilized a 35-question questionnaire covering personal information, medical history, and dietary health assessments. Findings revealed that only 31% of pre-dialysis patients had adequate knowledge of food management systems to enhance dialysis and treatment protocols, whereas 69% of hemodialysis patients understood their dietary needs but did not follow a proper diet. Among hemodialysis patients, 63% experienced loss of appetite and sudden weight loss, with 16% unable to regain their baseline weight and facing protein-energy wasting [PEW]. A staggering 99% reported symptoms of short-term hyperphosphatemia, with 55% using Reangle pills for relief, while 44% did not due to financial reasons or lack of awareness. Hypertension affected 40% of post-dialysis patients, and 38% experienced edema and shortness of breath, emphasizing better fluid regulation. In conclusion, while a majority of CKD patients were aware of their dietary needs, many struggled with appetite loss and weight issues, leading to significant nutrient deficiencies and complications. مرض الكلى المزمن هو مرض منتشر على نطاق واسع في العالم، وهو يؤدي إلى خلل دائم في وظائف الكلى وخاصة في مراحل المرض المتقدمة، مما يستلزم تدخلات مثل غسيل الكلى أو زرع الكلى. في الآونة الأخيرة، أوضحت نتائج البحوث العلمية أن التدخلات الغذائية لمريض الكلى تعتبر إلزامية لمواجهة الآثار السلبية لهذا المرض، وخاصة بالنسبة للمرضى الذين يخضعون لغسيل الكلى. تهدف هذه الدراسة إلى تقييم وعي مرضى الكلى المزمن بالعلاقة بين تناول النظام الغذائي المناسب ومضاعفات المرض، مع التركيز علي تأثير تناول الفوسفور والصوديوم على معدل الإصابة والوفيات لدى مرضى الكلى المزمن. أجرت الدراسة مقابلات مع 111 مريضًا يخضعون لغسيل الكلى في مركزين لغسيل الكلى في طرابلس، ليبيا. استخدمت الدراسة استبيانًا مكونًا من 35 سؤالاً يغطي المعلومات الشخصية والتاريخ الطبي وتقييمات للمستوى التغذوي للمرضى، ومدي وعي المرضى بتأثير الغذاء على حالتهم الصحية. كشفت النتائج أن 31٪ فقط من مرضى ما قبل غسيل الكلى لديهم معرفة كافية بأنظمة إدارة الأغذية لتعزيز غسيل الكلى وبروتوكولات العلاج، في حين أن 69٪ من مرضى غسيل الكلى يفهمون احتياجاتهم الغذائية ولكنهم لم يتبعوا نظامًا غذائيًا سليمًا. ومن بين مرضى غسيل الكلى، عانى 63% من فقدان الشهية وفقدان الوزن المفاجئ، ولم يتمكن 16% من استعادة وزنهم الأساسي ويواجهون إهدار البروتين والطاقة. وأبلغ 99% عن أعراض فرط فوسفات الدم قصير المدى، حيث استخدم 55% حبوب Reangle لتخفيف الأعراض، بينما لم يفعل 44% ذلك لأسباب مالية أو قلة الوعي. أثر ارتفاع ضغط الدم على 40% من مرضى ما بعد غسيل الكلى، و38% عانوا من الوذمة وضيق التنفس، مما يؤكد على تنظيم السوائل بشكل أفضل. وفي الختام، بينما كان غالبية مرضى الفشل الكلوي المزمن على دراية باحتياجاتهم الغذائية، عانى الكثيرون من فقدان الشهية ومشاكل الوزن، مما أدى إلى نقص كبير في العناصر الغذائية وحدوث مضاعفات للمرض